Behavioral Management and Financial Decision-Making: A Literature Review on the Impact of Organizational Culture on Corporate Financial Strategies - Riu, Isma Azis (PT Maju Malaqbi Makkarana, 2024)
This study aims to explore the integration of behavioral management and corporate finance and provide strategies to improve overall corporate performance. The research method used is a review of related literature and research. A qualitative and descriptive approach was used to analyze the relationship between behavioral and financial management in a corporate context. The results show that effective integration between behavioral and financial management can increase employee productivity, improve financial decision-making, and build a strong organizational culture. The necessary strategies include proper recruitment, continuous employee development, effective communication, behavioral financial decision-making, and comprehensive performance evaluation. By implementing this approach, companies can achieve better financial performance and reach their long-term goals.